2014
DOI: 10.1007/s00128-014-1320-8
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Blood of Sea Turtles Lepidochelys olivacea in the Gulf of California, Mexico

Abstract: This study determined the concentrations of heavy metals in blood collected from Pacific Ridley sea turtles (Lepidochelys olivacea) inhabiting the coast of Guasave, Mexico, in the Gulf of California. The highest reported metal concentration in blood was Zn, followed by Se. Of nonessential toxic metals, As was reported in higher percentage compared to Cd. The concentrations of metals detected were present as follows: Zn > Se > Mn > As > Ni > Cd > Cu. Cd concentration in blood is higher in our population in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…Previous studies in this area have confirmed the presence of five of the seven sea turtle species known worldwide. Of these five species, the olive ridley is the most abundant [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in this area have confirmed the presence of five of the seven sea turtle species known worldwide. Of these five species, the olive ridley is the most abundant [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, methoxychlor, endrin, and heptachlor levels in the Navachiste-Macapule lagoon system suggested that these compounds were continuously applied although their use is forbidden (Montes et al, 2012 ). Several recent studies evaluating heavy metals and their potential impact on sea turtles in Northwestern Mexico have been reported (Frías-Espericueta et al, 2006 ; Ley-Quinonez et al, 2011 ; Ley-Quiñónez et al, 2013 ; Zavala-Norzagaray et al, 2014 ). The region encompasses the northern nesting and feeding distribution for black ( Chelonia mydas agassizii ) and olive ridley ( Lepidochelys olivacea ) turtles (Ley-Quiñónez et al, 2013 ; Aguilar-Gonzalez et al, 2014 ; Zavala-Norzagaray et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies evaluating heavy metals and their potential impact on sea turtles in Northwestern Mexico have been reported (Frías-Espericueta et al, 2006 ; Ley-Quinonez et al, 2011 ; Ley-Quiñónez et al, 2013 ; Zavala-Norzagaray et al, 2014 ). The region encompasses the northern nesting and feeding distribution for black ( Chelonia mydas agassizii ) and olive ridley ( Lepidochelys olivacea ) turtles (Ley-Quiñónez et al, 2013 ; Aguilar-Gonzalez et al, 2014 ; Zavala-Norzagaray et al, 2014 ). The effects of heavy metals and other environmental contaminants in sea turtles have been previously documented as one of the potential synergic etiologies of marine turtle fibropapillomatosis (Aguirre et al, 1994 , 2006 ; Lutcavage et al, 1997 ; Aguirre and Lutz, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, haematological methods are the most widely used as indicators of sea turtle health, since they provide information on immune, cellular and humoral factors, which are necessary for the response to adverse factors, through the blood which can indicate pathological changes in the organisms. Therefore, blood parameters are a noninvasive diagnostic tool that can be used to evaluate and monitor the health status of wildlife [33].…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…However, in the case of sea turtles, there is difficulty in defining the blood reference values considered normal parameters due to the variability between sea turtles' geographic areas, ecological habitat, populations, sexual maturity, reproductive status, diet and migration. For this reason, therefore, blood parameters must be established for each species and region [31,33].…”
Section: Biochemical Studiesmentioning
confidence: 99%